Sanksi Hukum Terhadap Tenaga Medis dalam Melaksanakan Tugas Apabila Terjadi Malpraktik di UPT.Puskesmas Kintamani II Kabupaten Bangli - I Kadek Roger Budiastra; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Jurnal Analogi Hukum, 2024)
Medical malpractice has specific regulations for doctors regarding medical procedures, and mistakes committed can be punished. The problem is how to apply legal sanctions for medical personnel who commit malpractice in UPT. Kintamani II Health Center, Bangli Regency? dAnd how are the obstacles faced by UPT. Kintamani II Health Center, Bangli Regency, if there are medical personnel who commit malpractice? This study used empirical legal research. Sanctions for medical personnel who commit malpractice at UPT. Puskesmas Kintamani II, has been regulated in Law Number 23 of 1992 concerning health and medical code of ethics. Obstacles faced by UPT. Kintamani II Health Center is an internal constraint on the number of human resources that will be reduced so that services will be less optimal while external lack of public trust in medical personnel on duty.